House Season 1 Disc 5 - Laurie, Hugh, 1959-; Universal City Studios; Universal Studios Home Entertainment (Firm); Fox Broadcasting Company (Universal City, CA : Universal Studios Home Entertainment, 2007)
Dr. Gregory House is a brilliant physician who is devoid of any bedside manner. While his behavior can border on antisocial, Dr. House thrives on the challenges that other doctors shy away from. Together with his hand-picked team of young doctors, he'll do whatever it takes to solve the case.
Role model -- Babies and bathwater -- Kids -- Love hurts.
Title from disc label.
Originally broadcast as episodes of the television series on Fox in 2004.
Hugh Laurie.
Not rated.
DVD, NTSC, Dolby Digital English 5.1, anamorphic widescreen, dual layer.
Subtitles for the deaf and hard of hearing.
Keywords: Medical drama; Medical ethics -- Drama; Drama; Medical television programs; Television programs; Video recordings for the hearing impaired